Design and Testing of a GNSS Reflectometry CubeSat Payload for Monitoring Climate Change - Chan, Gary (University of Waterloo, 2017)
This thesis presents an alternative method for using reflected global navigation satellite systems (GNSS) signals as a remote sensing technology. The method aims to reduce the costs required so that the technology can be used on a CubeSat for the purpose of monitor Canadian arctic sea ice. The presence and age of sea ice can be determined by estimating the dielectric properties. In order to verify the hardware designed for this method, the system is placed on a quadcopter and own near Columbia Lake at the University of Waterloo. Multiple sets of data are recorded and analyzed using the proposed method. The results show that the system is able to differentiate between water and land, with the potential for this method to identify and monitor sea ice in the arctic.